Role of N6-Methyladenosine (m6A) epitranscriptomic mark in regulating viral infections and target for antiviral development - Bayoumi, Mahmoud; Manju, Vidya; Martinez-Sobrido, Luis; Munir, Muhammad (Frontiers in Pharmacology, 2025)
Viral infectious diseases continue to pose significant public health threats, driving severe epidemics and occasional pandemics of great consequences to humans. Viral infections trigger a range of transcriptional and epitranscriptional changes, including N6-methyladenosine (m6A) modification—one of the most abundant and dynamic RNA methylation marks. Although m6A mark was identified decades ago, its functional relevance in viral RNA remained elusive until recent advances in sequencing technologies. Viruses, like their host cells, depend on mRNA for protein synthesis and must rapidly replicate and evade host immune responses. This review focuses on the critical role of m6A in the regulation of viral infections and immune responses. Herein, we explore the most recent advances on how viruses exploit the m6A marks and host m6A machinery to enhance their replication and how host m6A modifications can influence viral pathogenicity. Understanding the interplay between m6A modifications and viral life cycles will be important for the potential of targeting m6A regulatory proteins as novel antiviral strategies to control viral infections. Moreover, a better understanding of these mechanisms will contribute to deeper insights into the host innate immune response and the development of innovative antiviral therapeutics.